Testing Business Models for Paid Mobile App: An Empirical Study - Artur Samojluk; Karolina Papiernik (Communications of International Proceedings, 2022)
This paper explores the issues relating to the analysis of business models by mobile app developers. The research objective is to determine which pricing model for internal services in mobile applications is optimal. An experimental study of the market for paid mobile applications and games was conducted, allowing the conclusion of an optimal business model, which is one of the factors of market success. The paper also presents the mobile app and games market in recent years and the changes it has gone through. The most important success factors common to the most profitable mobile applications are discussed.